Construction and characterization of a reverse genetics system of bovine parainfluenza virus type 3c as a tool for rapid screening of antivirals in vitro - Han, Yu; Lu, Kejia; Zhang, Riteng; Wei, Xi; Guo, Hanwei; Tong, Lina; Wang, Xinglong; Xiao, Sa; Liu, Haijin; Yang, Zengqi (Frontiers in Veterinary Science, 2024)
Bovine parainfluenza virus type 3 (BPIV3) is a key pathogen associated with Bovine respiratory disease complex (BRDC). However, its specific pathogenesis mechanisms have not been fully elucidated. Reverse genetics provides a useful method for understanding the pathogenic mechanism of BPIV3. To ensure the rescue platforms function, we first build a minigenome (MG) system of BPIV3 utilizing a 5-plasmid system in this investigation. Then, we obtained a full-length infection clone of BPIV3 from the SX-2021 strain, and different methods identified the rescued virus.Additionally, we recover a recombinant BPIV3 using the reverse genetics system that could express enhanced green fluorescence protein (eGFP). Through the growth curve assays, the replicate capability of rBPIV3-SX-EGFP was like that of the parental virus.Subsequently, the rBPIV3-SX-EGFP was used for determining the antiviral activity of ribavirin, the result showed that ribavirin had an anti-BPIV3 effect in MDBK cells. In conclusion, the successful development of a reverse genetic system for the SX2021 strain establishes a foundation for future studies on BPIV3, including investigations into its pathogenic mechanism, gene function, and antiviral screening.